Pengaruh Pemberian Ekstrak Kecambah, Ekstrak Tomat dan Pupuk Cair Hayati pada Pertumbuhan Seedling Manggis (Garcinia mangostana L.) - Karyanto, Agus; Pramono, Sudi; Rugayah, Rugayah; Fauzan, Naufal Dani (JURNAL AGROTROPIKA, 2022)
The slow initial growth of mangosteen is caused by poor rooting, especially secondary roots and root hairs. Therefore, technology is needed to stimulate root growth so that the absorption of nutrients in the soil becomes effective. This study used mung bean sprout extracts and tomato extracts as natural plant growth regulators (PGRs) combined with the use of biological liquid fertilizers. This research was conducted in the greenhouse of the Horticulture Building, Department of Agronomy and Horticulture, Faculty of Agriculture, University of Lampung from March 2020 to July 2020. The treatments were arranged in a factorial (3x2) in a randomized block design which was repeated 3 times. The first factor was natural PGR, which consists of: without natural PGR, mung bean sprout extract, and a mixture of sprout and tomato extract. The second factor was biological liquid fertilizer, which consists of control and with biological liquid fertilizer. The homogeneity of variance was tested by the Bartlett test, while the data additivity test was tested by the Tukey test. If the assumptions were met, the data was then analyzed by means of variance. The difference in the mean value was tested with LSD at the 5% level. The results showed that the administration of natural PGRs and biological liquid fertilizer did not show a significant effect on all the variables tested. The growth of most seedlings were upnormal due to the presence of root-attacking insect larvae previosuly present in the growing media. With minor disturbance from insect, the control plants showed better plant height (1.85 cm), number of leaves (3.28 pieces), leaf area (15.21 cm2), primary root length ( 3.77 cm), the number of secondary roots (2 strands), and plant fresh weight (3.55 g) than the treatments. Keywords : biological liquid fertilizer, mangosteen, natural PGR